Active Deception Detection. (October 2014) - Levine, Timothy R.
Actively detecting deception requires (a) gathering information for fact-checking the communication content, (b) strategically prompting deception cues, and (c) encouraging honest admissions and discouraging continued deceit. Most deception-detection research, active or otherwise, finds that people are only slightly better than chance at correctly distinguishing truth from lies. Poor accuracy stems from a lack of reliable deception cues that hold across people and situations. Consequently, basing lie detection on deception cues is prone to error. However, some approaches to active deception detection yield higher accuracy than passive observation. Not all active approaches are advantageous. Mere interaction and mere question-asking produce outcomes similar to passive observation. Evidence-based and confession-solicitation approaches can be highly effective: for example, strategic use of evidence (SUE) and the content in context approach.